2008
DOI: 10.1007/s10661-007-0140-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of Azolla pinnata and Vallisneria spiralis in Hg removal from G.B. Pant Sagar of Singrauli Industrial region, India

Abstract: The aim of the present work was to monitor the Hg pollution in water and sediments of G.B. Pant Sagar located in Singrauli Industrial Region, India and to suggest the efficient aquatic plants for its phytoremediation. The study assessed the comparative potential of a free floating water fern Azolla pinnata and submerged aquatic macrophyte Vallisneria spiralis to purify waters polluted by Hg. Six days laboratory experiments have been conducted to mark the percentage removal of Hg at initial concentration of 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…This suggested that the Cd-induced change in color of fronds might be due to the decrease in chlorophyll and carotenoids while the increase in total phenolics and their biosynthesis-related PAL play a role in detoxification of Cd in A. imbricata. Rai and Tripathi (2009) found a concentration-dependent decrease in the content of chlorophyll a, protein, RNA, and DNA, and nutrient (nitrate and phosphate) uptake was detected in A. pinnata because of Hg toxicity. Sánchez-Viveros et al (2010) reported that heavy metal copper disrupted photosystem II resulting in drop in potential phytochemical yield at higher concentrations in A. filiculoides and A. caroliniana.…”
Section: Biochemical Effectsmentioning
confidence: 88%
See 3 more Smart Citations
“…This suggested that the Cd-induced change in color of fronds might be due to the decrease in chlorophyll and carotenoids while the increase in total phenolics and their biosynthesis-related PAL play a role in detoxification of Cd in A. imbricata. Rai and Tripathi (2009) found a concentration-dependent decrease in the content of chlorophyll a, protein, RNA, and DNA, and nutrient (nitrate and phosphate) uptake was detected in A. pinnata because of Hg toxicity. Sánchez-Viveros et al (2010) reported that heavy metal copper disrupted photosystem II resulting in drop in potential phytochemical yield at higher concentrations in A. filiculoides and A. caroliniana.…”
Section: Biochemical Effectsmentioning
confidence: 88%
“…Increasing environmental awareness and concern has attracted scientific community to extend its exploitation more vigorously in the area of phytoremediation because the fern can hyperaccumulate variety of pollutants such as heavy metals, radionuclides, dyes, and pesticides etc. from aquatic ecosystems along with other macrophytes (Padmesh et al 2006;Rai and Tripathi 2009;Mashkani and Ghazvini 2009;Sood et al 2011). This fern has many features that prove it as a better plant system than many other macrophytes, which include:…”
Section: Azolla-a Better Macrophyte For Phytoremediationmentioning
confidence: 99%
See 2 more Smart Citations
“…(family Hydrocharitaceae; common name: 'flat grass', 'noodle grass' and 'channel grass') is widely distributed in shallowwater lakes in Asia and growing well in good transparence, deep-thick silt and slow-flow water areas (Sun 1992). V. spiralis plays a significant role in decreasing eutrophication of water body for its productivity and disposing industrial wastewater for its adaptability and well potential pollutant absorption (Xian et al 2006), and it has also been shown to accumulate significantly high amount of heavy metals from water bodies, including copper and cadmium (Sinha et al 1994;Gupta and Chandra 1998;Sinha et al 2002), and its phytoremediation effect of heavy metals from water is well documented (Rai and Tripathi 2009). However, little is known about the ability of this plant to accumulate toxic metals from sediments, especially when heavy metals are applied in moderately high concentration.…”
Section: Introductionmentioning
confidence: 99%